Police and Mental health: Exploring Co-Response Models and Best Practices - Eloi, Bianca; Shemin, Addison; Feinman, Anna; Yepez-Coello, Francesco; Brown, Jacie; Joseph, Roshni; Schumacher, Matthew; Bongar, Bruce (International Journal of Police Science, 2025)
Crisis related to mental health or substance use is creating an increased challenge for emergency departments and law enforcement. Between 5% and 15% of all 911 calls are related to a mental health crisis, making police officers the first to respond and jail or the emergency department the likely outcome[i]. While the responsibility of responding to mental health calls has shifted to law enforcement agencies, there remains concern about training for both mental health clinicians and law enforcement on interventions and effectiveness in how to respond to an individual in a mental health crisis. Several versions of police-mental health partnership programs were created to address the need for community mental health response. Several jurisdictions have chosen to implement different contexts and forms of co-response programs, and the lack of research regarding the outcomes has created questions as to the effectiveness of co-response programs [ii]The mental health responders that comprise one-half of the co-response team are integral to the success of this type of programming. Because there is a lack of centralized prerequisites for individuals seeking employment in this capacity, the education, experience, and background requirements are far from standard. Likewise, training for law enforcement officers varies by jurisdiction and co-response model. The paper aims to comprehensively review current best practices and identify gaps in training and program outcomes for further research.